El mejoramiento genético de la habichuela en América Latina: memorias de un taller, CIAT, Cali, Colombia, 11 al 15 de mayo de 1987 - Davis, J.H.C.; Janssen, W. (International Center for Tropical Agriculture, 1987)
The purpose of the 1st Latin American workshop on snap bean improvement was to define objectives and strategies for crop improvement and discuss the relationship between an international center for agricultural research and the national programs. The relationships between the public and private sectors regarding snap bean improvement are also discussed. The papers and discussions presented during the workshop are also included. The importance of including snap bean improvement as a research line in CIAT in its different aspects (sanity, improvement, economics, and statistics) was emphasized. All the participants in the meeting were committed to generate in their countries the necessary research to achieve real progress in the topic and serve growers all over the world. (CIAT)